Molecular Polar Surface Area, Total Solvent Accessible Surface Area (SASA), Heat of Formation, and Gamma-Ray Attenuation Properties of Some Flavonoids - Tekin, Huseyin Ozan; ALMisned, Ghada; Issa, Shams A. M.; Kasikci, Emel Serdaroglu; Arooj, Mahreen; Ene, Antoaneta; Al-Buriahi, M. S.; Konuk, Muhsin; Zakaly, Hesham M. H. (Frontiers in Physics, 2022)
Abstract The chemical and physical characteristics of several flavonoid compounds such as geraniol, thymoquinone, betaine, apigenin, N-acetylcysteine, catechin, L-carnosine, epigallocatachin, and saponarin were examined in this work. Numerous molecular properties of all flavonoid compounds used in this study were calculated using the Calculate Molecular Properties module of Accelrys Discovery Studio (DS) v20.1.0.19295.0. These properties included molecular polar surface area, total solvent-accessible surface area, and heat of formation. We used the MCNPX general-purpose Monte Carlo code in combination with the Phy-X PSD software to determine gamma-ray interaction parameters such as attenuation coefficients, effective atomic numbers, and buildup factors. The findings indicate that the flavonoids' elemental compositions have a direct effect on their chemical and physical properties. Additionally, a synergistic interaction of chemical and physical behaviors has been observed. Among the flavonoids studied, saporanin was shown to have the highest polar surface area and solvent accessible surface area, as well as the highest stability. Additionally, saporanin had the strongest gamma-ray attenuation characteristics across a broad photon energy range. It may be inferred that saporanin's elemental structure enables a synergistic relationship between its chemical and physical characteristics. The findings of this study may contribute in the evaluation of saporanin's hypoglycemic, antibacterial, and hepatoprotective effects.